The Proterozoic P-T-t Evolution of the Kemp Land Coast, East Antarctica; Constraints from Si-saturated and Si-undersaturated Metapelites - Jacqueline Halpin; White, RW; Clarke, GL; Kelsey, DE (2007)
Integrated metamorphic and geochronological data place new constraints on the metamorphic evolution of a Neoproterozoic orogen in east Antarctica. Granulite-facies rocks from a 150km stretch of the Kemp Land coast reflect peak conditions involving T ≈ 870-990°C at P ≈ 74-10 kbar, with pressure increasing westward towards an Archaean craton. Electron microprobe-derived (Th + U)-Pb monazite ages from metapelitic assemblages indicate that the major mineral textures in these rocks developed during the c. 940Ma Rayner Orogeny. Complex compositional zoning in monazite suggests high-T recrystallization over c Myr. Diversity in metapelitic reaction textures reflects silica and ferromagnesian content: Si-saturated Fe-rich metapelites contain garnet that is partially pseudomorphed by biotite and sillimanite, whereas Si-saturated Mg-rich metapelites and Si-undersaturated metapelitic pods have reaction microstructures involving cordierite enclosing orthopyroxene, garnet and/or sapphirine, cordierite sapphirine + symplectites around sillimanite and coarse-grained orthopyroxene + corundum separated by sapphirine coronae. Interpretations based on P-T pseudosections provide integrated bulk-rock constraints and indicate a clockwise P-T-t path characterized by a post-peak P-T trajectory with dP/dT ≈ 15-20 bar/°C. This moderately sloped decompressive-cooling P-T path is in contrast to near-isothermal decompression P-T paths commonly cited for this region of the Rayner Complex, with implications for the post-collisional tectonic response of the mid- to lower crust within this orogenic belt. © The Author 2007. Published by Oxford University Press. All rights reserved.